KAJIAN HUKUM MENGENAI PENGANGKATAN HAKIM KONSTITUSI OLEH PRESIDEN DITINJAU DARI PRINSIP TRANSPARANSI DAN PARTISIPASI - Sabungan Sibarani (PROSIDING SEMINAR NASIONAL CENDEKIAWAN, 2018)
The appointment mechanism of the Constitutional Court Judge is different from that of an ordinary judge or Supreme Court Justices, Constitutional Court Judges totaling nine persons consisting of three persons elected by the People's Legislative Assembly, three elected by the President, and three by the Supreme Court. Where in this case, the nomination of Constitutional Justices is conducted in a transparent and participative manner, meaning that in the process of selecting Constitutional Justices, it must be conducted through a transparent selection process and involves the active participation of the community. The President is authorized to propose three judges of the composition of nine Constitutional Judges and is the prerogative of the President of the proposed nominee. The appointment mechanism and recruitment system of candidates for Constitution Justice by the President should be as mandated by Article 19 of the Law of the Republic of Indonesia Number 8 Year 2011 on Amendment to Law Number 24 Year 2003 regarding Constitutional Court which must fulfill the principles of transparency and participation. In addition, the Government should make clearer rules on the appointment mechanism of Constitutional Justices especially regarding internal selection to be more transparent.